Microstructural Changes in Compressed Cervical Spinal Cord Are Consistent With Clinical Symptoms and Symptom Duration. Issue 16 (15th August 2020) - Wu, Weifei; Yang, Zong; Zhang, Tingting; Ru, Neng; Zhang, Fan; Wu, Bin; Liang, Jie
Abstract : Study Design: A prospective study. Objective: To investigate the association between microstructural changes measured by diffusion tensor imaging (DTI) and clinical symptoms and their duration in patients with cervical spondylotic myelopathy (CSM) affected by single level. Summary of Background Data: No report was reported regarding the association between the microstructural changes and the symptoms and their duration at single-level spinal cord compression. Methods: Twenty-nine consecutive patients with CSM and 29 normal subjects were enrolled in this study. DTI with tractography was performed on the cervical spinal cord. Clinical symptoms were evaluated using modified Japanese Orthopaedic Association (mJOA) scores for each patient, and the duration of clinical symptoms was noted based on the earliest instance of limb pain or numbness or weakness or bladder dysfunction. Mean fractional anisotropy (FA) and apparent diffusion coefficient (ADC) values were calculated from tractography images. Results: The mean FA value of the cervical compressed spinal cord was significantly lower than the FA of the normal population ( P < 0.001). The mean ADC value in the cervical compressed spinal cord was obviously higher than those of normal cervical spinal cord ( P < 0.001). In the CSM patients, a significant positive association was observed between FA values and mJOA scores ( P < 0.001). However, there were a notable negative association between mJOA scores and ADC values ( P < 0.001), and between mJOA scores and symptom duration ( P < 0.001). Conclusion: These results illustrate DTI can measure the micostructural changes of cervical spinal cord and DTI parameters are potential biomarkers for spinal cord dysfunction in patients with CSM. Level of Evidence: 3 Abstract : Diffusion tensor imaging with tractography was performed on the cervical spinal cord in patients with cervical spondylotic myelopathy and 29 normal subjects. Fractional anisotropy (FA) and apparent diffusion coefficient (ADC) values were calculated from tractography images. The mean FA/ADC value of the cervical compressed spinal cord was significantly lower than the FA/ADC of the normal population.